Adrenal Cortex: From Physiology to Disease - Pierre Val (Frontiers Research Topics, 2016)
The adrenal gland plays essential roles in the control of body homeostasis, stress and immune responses. The adrenal cortex represents up to 90% of the gland and is specialised in the production of mineralocorticoids, glucocorticoids and adrenal androgens. This production is tightly coordinated and results from a unique zonal organisation. Although our knowledge of the molecular mechanisms controlling adrenal steroidogenesis is quite extensive, for decades, the mechanisms of adrenal cortex development, cellular homeostasis and renewal have remained elusive. The advent of new high-throughput technologies and sophisticated genetic approaches has brought tremendous progress in our understanding of how the adrenal cortex achieves and maintains its particular organisation. The aim of this Frontiers in Endocrinology Topic is to provide readers with a snapshot of our current knowledge on adrenal physiology and how deregulations of these processes result in adrenal diseases. This includes but is not limited to, basic research on adrenal development, cell lineage identification, progenitor cells, tissue renewal, control of differentiation and zonation and clinical research on the identification of disease-related genes.